Short‐Term Efficacy of Different First‐Line Chemotherapy Regimens for Advanced Non‐Small Cell Lung Cancer: A Network Meta‐Analysis - Bei‐Bei Zhang; Weibo Zhu; Jun Tao; Yun Li; Chuan‐Chong Du; Yun‐Xia Chen; Yan‐Dong Liu (Wiley, 2020)
This study intends to compare short‐term efficacy of 12 chemotherapy regimens in treatment of advanced non‐small cell lung cancer (NSCLC) by a network meta‐analysis (NMA). PubMed, Cochrane Library, and Embase were searched from the inception of each database to June 2018. Randomized controlled trials (RCTs) of the 12 chemotherapy regimens for advanced NSCLC were included. Direct and indirect evidence were combined by NMA to evaluate the odds ratio and the surface under the cumulative ranking curves (SUCRA) of the 12 chemotherapy regimens. Nineteen RCTs that met our inclusion criteria were collected in this study. For partial response (PR), gemcitabine exhibited relatively poor efficacy compared with cisplatin + gemcitabine, carboplatin + gemcitabine, carboplatin + paclitaxel, paclitaxel + gemcitabine, and cisplatin + gemcitabine + vinorelbine. For overall response rate (ORR), gemcitabine had poorer efficacy than cisplatin + gemcitabine and paclitaxel + gemcitabine. For disease control rate (DCR), compared with carboplatin + gemcitabine and gemcitabine, paclitaxel + gemcitabine had a better efficacy. Gemcitabine had the lowest SUCRA values in terms of complete response, PR, ORR, stable disease, and DCR; whereas paclitaxel + gemcitabine ranked the highest in ORR, progressive disease, and DCR. The cluster analysis revealed that cisplatin + gemcitabine, paclitaxel + gemcitabine, and cisplatin + gemcitabine + vinorelbine had better short‐term efficacy for advanced NSCLC. Collectively, short‐term efficacy of multidrug combination chemotherapy regimens was superior to that of single‐drug chemotherapy regimens for advanced NSCLC. Cisplatin + gemcitabine, paclitaxel + gemcitabine, and cisplatin + gemcitabine + vinorelbine may have particularly prominent short‐term efficacy for advanced NSCLC.